Hubungan Antara Efikasi Diri dengan Kemampuan Berpikir Kritis Mahasiswa Fakultas Ilmu Keperawatan Unissula - mundhofar, aziz mahendra; Issroviatiningrum, Retno; Abdurrouf, Muh (Journal of Nursing Invention, 2025)
Background: Efficacy is a person's way of doing something in order to improve the maximum quality of learning. The ability to think critically in dealing with very busy lectures has a significant influence on learning. Objective: This research aims to examine the relationship between Self-Efficacy and Critical Thinking Ability in students at the Faculty of Nursing, Sultan Agung Islamic University, Semarang.Method: This research applies a quantitative approach with a cross-sectional design. This research involved 141 respondents who were selected through purposive sampling, namely a sample selection technique based on predetermined criteria. The data collected was then analyzed using the Spearman rank test. The questionnaire used is in the form of a Likert scale with each variable consisting of 25 questions. Results: Research that has been carried out shows that the majority of respondents are in the high category with 83 respondents (58.87%). Critical Thinking Ability is in the high category with 110 respondents (78.29%). The statistical test results obtained a p-value of 0.000 (<0.05) which means there is a relationship between Self-Efficacy and the Critical Thinking Ability of Unissula Nursing Faculty Students. Conclusion: Self-efficacy and critical thinking skills in Nursing students at Sultan Agung Islamic University Semarang have a significant relationship. This relationship is positive with moderate closeness (0.496) and a very low p-value (0.000) which indicates that increasing self-efficacy is related to increasing critical thinking abilities.Keywords: Self-Efficacy and Critical Thinking Ability